2016
DOI: 10.1002/adem.201600057
|View full text |Cite
|
Sign up to set email alerts
|

Polyphosphate as a Bioactive and Biodegradable Implant Material: Induction of Bone Regeneration in Rats

Abstract: Inorganic polyphosphate (polyP) is a naturally occurring polymer that is bioresorbable and anabolically active on bone forming cells in vitro. In order to demonstrate if polyP also shows morphogenetic activity in vivo, animal studies are performed applying the rat calvarial defect model. Poly(D,L-lactide-co-glycolide) (PLGA) microspheres with a narrow size distribution (%820 mm) are prepared, containing either encapsulated polyP or b-tricalcium phosphate (b-TCP), used as a reference material. Discs are prepare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 54 publications
1
22
0
Order By: Relevance
“…166 A further gene anabolically implicated during bone formation, collagen type I 190 is also strongly upregulated in the presence of these particles, while b-TCP caused no effect. 191 Scaffold architecture: for small defects the sphere technology has been applied until now. In anticipation of future animal studies a preparation technology has been introduced for larger implants.…”
Section: Characteristics Of Ca-polyp-mp For Bone Implantsmentioning
confidence: 99%
See 1 more Smart Citation
“…166 A further gene anabolically implicated during bone formation, collagen type I 190 is also strongly upregulated in the presence of these particles, while b-TCP caused no effect. 191 Scaffold architecture: for small defects the sphere technology has been applied until now. In anticipation of future animal studies a preparation technology has been introduced for larger implants.…”
Section: Characteristics Of Ca-polyp-mp For Bone Implantsmentioning
confidence: 99%
“…Those spheres have been implanted into cranial defects and were shown to undergo dissolution during a 4-week period in rats. 166,191 This initial phase is accompanied by an invasion of new cells, comprising bone-mineralizing activity (Fig. 14).…”
Section: Single-phase Polyp-based Spheresmentioning
confidence: 99%
“…In addition, polyP has been proven to function as extracellular fuel deposit allowing, after enzymatic cleavage of the phosphoanhydride bonds by the alkaline phosphatase [ALP], the transfer of the released metabolic energy to ADP and AMP . The polymer can be characterized as being smart because it exhibits different and specific functions according to the counterion (cation) [Ca 2+ , Mg 2+ , or Sr 2+ ] used for salt/nanoparticle formation such as Ca–polyP and Sr–polyP for acceleration of bone regeneration or Mg–polyP for cartilage repair . Since to date polyP has the most promising future as a biomaterial/scaffold for bone implants, we have selected for the present study the Ca 2+ –polyP salt.…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that polyP particles can be incorporated in a straightforward way into pearls or implants, e.g., by embedding them into poly( d , l -lactide- co -glycolide) [ 44 , 75 ], which proved firstly, to accelerate the physiological bone regeneration, and secondly, to be superior than β-tricalcium phosphate. In addition, such a scaffold material allows MSC to proliferate.…”
Section: Discussionmentioning
confidence: 99%